Upaya Peningkatan Capaian Kepatuhan Program Rujuk Balik di RS X dengan Menggunakan Problem Solving Cycle - Fadilla Delima Sandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to achieve the target indicators for recruiting DRR participants that BPJS has set by 25% of the seven hands that BPJS Health has determined. The method used is the descriptive research method. The results showed that the DRR participant recruitment target indicator was not achieved due to low visits to the polyclinic, so the DPJP was worried that the patient would run out. No one would seek treatment at the hospital. They are achieving the target of the referral program recruitment participants set by the hospital with an increase of 10% every month. Hospital promotion program activities must be monitored regularly and involve related units. Keywords: Compliance, Referback Program, Problem Solving Cycle